Efektivitas Konsultasi Online di Puskesmas Pondok Betung Kota Tangerang Selatan - Varadella Kusumawardhani; Nida Handayani (Jurnal Media Administrasi, 2024)
Online consultation is an idea from e-government in the health services sector that uses technology to integrate health services at Community Health Centers. The aim is to simplify bureaucratic processes in health services to the community. In practice, there are still several obstacles that arise, such as a lack of outreach efforts, slow response times from consultations, and recording that is not automatic because it still relies on WhatsApp. The aim of this research is to determine the effectiveness of "online consultation" to improve the quality of public services at the Pondok Betung Community Health Center, South Tangerang City. The method in this research is a qualitative method with a descriptive approach. Data collection techniques using observation, interviews and documentation as complements. This research was analyzed using 4 (four) indicators of effectiveness, namely: (1) Accuracy of Program Targets, (2) Program Socialization, (3) Achievement of Program Objectives, and (4) Program Monitoring. The research results show that the effectiveness of the "online consultation" service at the Pondok Betung Community Health Center has not been achieved because there are still many people who do not know the information about this service. The socialization program for this service is not yet optimal because many people are still not aware of its existence. The program's objectives have also not been achieved well because the "online consultation" service has not been running smoothly and only a small number of people are using it. From the results of this research, it is concluded that online health services at the Pondok Betung Community Health Center, South Tangerang City have not reached the expected level of effectiveness.